OPTIMASI KEKUATAN TARIK KERTAS TISU DENGAN DESIGN OF EXPERIMENTS - Welly Sugianto (Institut Teknologi Adhi Tama Surabaya, 2026)
This study was conducted to identify factors that affect the tensile strength and tear strength of tissue paper. The variables studied for their impact on tensile strength are water concentration, amine concentration, chitosan concentration and pulp type concentration. The impact of these variables on the response was studied using the design of experiments. The design used was a full design where the design is an orthogonal design where there is no correlation between the independent variables. The experiment was replicated four times so that the degrees of freedom are sufficient to calculate the effect of a single factor and the interaction of more than three factors on the response. Significance testing is carried out using the F test and t test. The first experiments aim to identify factors that have a dominant influence on the response. Furthermore, based on these results, the optimum point is determined using the steepest ascent. Furthermore, the analysis is continued with a second-order equation to detect curvature which is a sign of the optimum position. Tensile strength and tear strength are successfully optimized at a water content of 60%, a raisabond content of 2.18%, a chitosan content of 3.29%, and a pulp content of 39.03%.